Modelling prediction of gas release to improve quality of foods during low temperature storage - Chien-Shan Chiu; Ping-Hsiu Huang; Wen-Chien Lu; Po-Yuan Chiang; Po-Hsien Li (Journal of Agriculture and Food Research)
Modified atmosphere packaging (MAP) is widely used to reduce economic losses by extending the shelf-life of food products. This study aimed to develop an active MAP formulation component with sodium ascorbate, sodium carbonate, and ferrous sulfate, which was shown to be applicable at low temperatures (4 °C) while efficiently controlling O2 and producing 1.0 %–44.1 % CO2. Moreover, the predicted equations enabled the estimation of the O2 and CO2 contents. In the future, the dosage could be determined based on the gas content required for various applications in food, such as refrigerated fruits, vegetables, and meats. Currently, the active MCP formulation for the reaction proceeds smoothly at 5 °C. Despite its promise, it requires additional water, making it inconvenient. However, these findings provide new insights into how active MAP facilitates convenient and effective development.